A retrospective study on cervical intraepithelial lesions of low-grade and undetermined significance: evolution, associated factors and cytohistological correlation - Silva, Criseide; Almeida, Elia Cláudia Souza; Côbo, Eliângela de Castro; Zeferino, Valéria Fátima Machado; Murta, Eddie Fernando Cândido; Etchebehere, Renata Margarida (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVES: Cervical cancer is an important cause of morbidity and mortality throughout the world. There is some controversy about the factors that may be associated with infection by the human papillomavirus (HPV) that may favor or protect against evolution from a low-grade intraepithelial lesion to a high-grade intraepithelial lesion or invasive neoplasia. The objective here was to evaluate the evolution of low-grade intraepithelial lesions and squamous or glandular lesions of undetermined significance, the associated factors and cytohistological correlations. DESIGN AND SETTING: Retrospective study conducted in a public tertiary-level university hospital. METHODS: Information was obtained by reviewing patient records and/or colposcopy reports. A statistical analysis was performed using logistic regression, calculating the odds ratio and applying chisquare tests. RESULTS: Of the 3390 patients, 409 evolved to high-grade intraepithelial lesions, of which 354 had an initial diagnosis of HPV infection, 27 of squamous atypia of undetermined significance, 22 of low-grade intraepithelial lesions with or without cytological diagnosis of infection by associated HPV and six of glandular cell atypia of undetermined significance. CONCLUSIONS: Lactobacillus sp and bacterial vaginosis on the smears, smoking and immunodepression were factors associated with evolution. A single partner, use of hormonal contraceptives, lower parity, age and a cytological diagnosis of cytolytic vaginosis, T. vaginalis, Candida sp or cocci were factors associated with protection. With regard to cytohistological correlation, there was a 74.08% agreement among patients with high-grade lesions and a biopsy obtained during the same period.